Elite running performances: the result of genetics, epigenetics and nurture - Venkata, R. K. (MOJ Sports Medicine, 2017)
Elite runners both sprinters and endurance runners seem to be restricted mostly to African race. There were researches on genetics and running performances of African runners with some favoring the concept of genetic predisposition of African runners whereas some others finding no such genetic link. This is a widely contested area of sports science and needs extensive research and intellectual reasoning. Though the genetic code of the human being was identified, the field of genetics is still has a long way to go in establishing the precision biodynamic of genetic interactions. The claim that certain level of consensus among scientists that the African runners are not predisposed with genetic endowment for running needs to be noticed and to be verified further. The fact is there is no single white or other race sprinter in men's 100 meters finals of Olympics since 1984. How can this happen if there is no genetic disposition for African runners, especially West African race runners towards sprinting. If only epigenetic factors like the training modules, diet, environment etc are playing role in this, the same may also can be adapted by other race runners. The Kalenjin tribe phenomenal success in distance running needs to be examined in terms of both genetics and epigenetic to try to find some reasonable answer for this long discussed but still inconclusive topic. The same is true with Ethiopian runners too. There may be somatotype advantages for these runners over European and other race runners as some are reasoning, like lighter calves and thinner and long legs, which again need to be ascribed to genetic adaptation to chronic environmental, activity stimuli which could have provided such advantage to move swiftly and to run for longer durations. But, another fact is that such somatotype advantages are there for many other African tribe and European tribe runners.1